2016
DOI: 10.1007/s10964-015-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Depressive Symptoms Between Heterosexual and Lesbian, Gay, and Bisexual Youth in a Dutch Cohort: The TRAILS Study

Abstract: Lesbian, gay, and bisexual (LGB) youth experience elevated levels of depressive symptoms compared to heterosexual youth. This study examined how differences in depressive symptoms between heterosexual and LGB youth developed from late childhood to early adulthood. The association between sexual orientation and depressive symptoms was estimated from age 11 to 22 using data from the TRacking Adolescents’ Individual Lives Survey, a longitudinal Dutch cohort study. Of the 1738 respondents (54.8 % girls) that provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
75
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 85 publications
(128 reference statements)
14
75
1
2
Order By: Relevance
“…In 2015, 14.8% of LGB males and 20.4% of LGB females suffered at least one major depressive episode, totaling 1.9 million individuals, compared to 4.3% of heterosexual males and 8% of heterosexual females [1]. These findings are consistent with other developed countries, and disparities are greater among bisexual adults [3,4].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In 2015, 14.8% of LGB males and 20.4% of LGB females suffered at least one major depressive episode, totaling 1.9 million individuals, compared to 4.3% of heterosexual males and 8% of heterosexual females [1]. These findings are consistent with other developed countries, and disparities are greater among bisexual adults [3,4].…”
Section: Introductionsupporting
confidence: 60%
“…Extraction forms included six categories of information: (1) study logistics (setting, country, publication year, study design, funding source), (2) study population characteristics (number of subjects, age, gender, race/ethnicity, sexual minorities included, education level, and income), (3) SMU (number of social networking sites, time of usage and frequency, scales, contextual measures), (4) health outcomes measured (primary and secondary outcomes measured and scales), (5) main results and limitations, and (6) appropriateness of reporting. To ensure accuracy, we implemented a quality control mechanism in which one reviewer completed a first data extraction and the second reviewer validated or disagreed with it.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…14,15 Consistent with this theory, empirical studies indicate that lower parental support, 16 increased parental rejection, 13 and more frequent peer harassment 17 or victimization 13,18 experienced by sexual minority adolescents contributed to higher depressive symptoms. However, these studies were typically focused on 1 or 2 psychosocial mediators in the parental or peer context.…”
mentioning
confidence: 78%
“…Past research revealed that victimization from both general bullying 19 and homophobic namecalling 20 was associated with higher depressive symptoms. Furthermore, peer harassment 17 or victimization 13 and sexual minority-related victimization 18 were significant mediators of the association between sexual minority status and depressive symptoms. However, empirical evidence on whether this extends to cyberbullying victimization remains unclear because traditional bullying was a stronger correlate of depression than cyberbullying victimization in 1 study.…”
mentioning
confidence: 91%
See 1 more Smart Citation